2011
DOI: 10.1074/jbc.m110.200980
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Cytosolic Glucose Levels during Differentiation of 3T3-L1 Fibroblasts into Adipocytes

Abstract: Cytosolic glucose concentration reflects the balance between glucose entry across the plasma membrane and cytosolic glucose utilization. In adipocytes, glucose utilization is considered very rapid, meaning that every glucose molecule entering the cytoplasm is quickly phosphorylated. Thus, the cytosolic free glucose concentration is considered to be negligible; however, it was never measured directly. In the present study, we monitored cytosolic glucose dynamics in 3T3-L1 fibroblasts and adipocytes by expressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 33 publications
6
18
0
Order By: Relevance
“…We applied the in‐cell calibration to calculate the intracellular glucose concentration in the intact HEK293T cells. In all the experimental conditions tested, medians of the calculated intracellular glucose concentrations were lower than the glucose concentration in the bath, similar to observations in other cultured cells imaged with different fluorescent biosensors (Kovacic et al, ; Zhang et al, ). This could reflect an inability of glucose transport to keep up with glucose consumption.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…We applied the in‐cell calibration to calculate the intracellular glucose concentration in the intact HEK293T cells. In all the experimental conditions tested, medians of the calculated intracellular glucose concentrations were lower than the glucose concentration in the bath, similar to observations in other cultured cells imaged with different fluorescent biosensors (Kovacic et al, ; Zhang et al, ). This could reflect an inability of glucose transport to keep up with glucose consumption.…”
Section: Resultssupporting
confidence: 86%
“…However, we observed that the intracellular [glucose] reported by the iGlucoSnFR‐TS fluorescence lifetime was consistently lower than the predicted value for full equilibration of intracellular [glucose] with glucose in the bath (Figures and ). This is similar to observations in cultured cells imaged with different fluorescent biosensors (Kovacic et al, ; Zhang et al, ). Indeed, metabolite levels do not necessarily match with metabolic fluxes since the concentration of a particular molecule will depend on the balance between consumption/production and transport (Jang, Chen, & Rabinowitz, ).…”
Section: Discussionsupporting
confidence: 89%
“…Prior to experiments, the cells were trypsinized and subcultured onto poly- L -lysine-coated coverslips. In separate subsets of experiments, the cultured rat lactotrophs and mouse embryonic fibroblast–adipose-like 3T3-L1 cells were prepared as described before (Kovacic et al,2011; Stenovec et al,2004). Unless stated otherwise, all chemicals were purchased from Sigma-Aldrich and were of highest purity grade available.…”
Section: Methodsmentioning
confidence: 99%
“…Some cells are lactate exporters, while others are lactate importers (Figure 4A). The concentration of a metabolite, absolute or relative, may be interesting in itself, as it informs about the balance between production and consumption (Fehr et al, 2003; Bittner et al, 2010, 2011; Takanaga and Frommer, 2010; Kovacic et al, 2011; Prebil et al, 2011). However, concentration gives no information about flux.…”
Section: Glucose Metabolism Measured With a Genetically-encoded Fret mentioning
confidence: 99%